Hybrid Perovskite Degradation from an Optical Perspective: A Spectroscopic Ellipsometry Study from the Deep Ultraviolet to the Middle Infrared - Tejada, A.; Peters, S.; Al-Ashouri, A.; Turren-Cruz, S.H.; Abate, A.; Albrecht, S.; Ruske, F.; Rech, B.; Guerra Torres, J.A.; Korte, L. (John Wiley and Sons, 2022)
A quantitative analysis of the thermally induced degradation of various device-relevant multi-cation hybrid perovskite films is performed using spectroscopic ellipsometry, for temperatures between 80 and 120 °C. The studied compositions are a triple cation perovskite Cs₀.₀₅(MA₀.₁₇FA₀.₈₃)₀.₉₅Pb(Br₀.₁₇I₀.₈₃)₃, a Rb-containing variant Rb₀.₀₅Cs₀.₀₅(MA₀.₁₇FA₀.₈₃)₀.₉₀Pb(Br₀.₁₇I₀.₈₃)₃, and a methylammonium-free Rb₀.₀₅Cs₀.₁₀FA₀.₈₅PbI₃ composition. A very wide combined spectral range of 200 nm to 25 μm is covered by combining the data from two separate instruments. The relative changes in organic cation concentrations are quantified from the middle infrared molecular absorption bands, leveraging the use of point-by-point fitting for increased sensitivity. Additionally, the formation of PbI₂ and non-perovskite δ-CsPbI₃ phases is evidenced from Bruggemann effective medium fits to the visible and ultraviolet complex refractive indices. Methylammonium is almost completely depleted from the relevant compositions within 100 to 285 min of thermal annealing. The MA-free perovskite degrades faster at intermediate temperatures, which is attributed to phase instability due to the formation of δ-CsPbI₃ in addition to PbI₂.
Keywords: Materials science; Ellipsometry; Perovskite (structure); Ultraviolet; Infrared; Analytical Chemistry (journal); Annealing (glass); Infrared spectroscopy; Thin film; Optics; Nanotechnology; Crystallography; Optoelectronics; Chemistry; Organic chemistry; https://purl.org/pe-repo/ocde/ford#1.04.00